In vitro and in silico analysis of L. donovani enoyl acyl carrier protein reductase - A possible drug target. Issue 16 (2nd November 2021) - Yadav, Shalini; Mandal, Haraprasad; Saravanan, Vijayakumar; Das, Pradeep; Singh, Shubhankar Kumar
Abstract: The emergence of increased resistance to the available drugs has created a situation that demands to find out more specific molecular drug targets for Leishmaniasis. The enoyl acyl carrier protein reductase (ENR), a regulatory enzyme in type II fatty acid synthesis, was confirmed as a novel drug target and triclosan as its specific inhibitor in many microorganisms. In this study, the triclosan was tested for the leishmanicidal property against Leishmania donovani ( L. donovani ) and the results of in vitro and ex vivo drug assays on promastigotes and amastigotes showed that triclosan possessed antileishmanial activity with a half minimal inhibitory concentration (IC50 ) of 30 µM. Consequently, adopting in silico approach, we have tested the triclosan's ability to bind with the L. donovani enoyl acyl carrier protein reductase ( Ld ENR). The 3D structure of Ld ENR was modelled, triclosan and cofactors were docked in Ld ENR model and molecular dynamic simulations were performed to observe the protein-ligands interactions, stability, compactness and binding energy calculation of the ligands- Ld ENR complexes. The observation showed that triclosan stably interacted with Ld ENR in presence of both the cofactors (NADPH and NADH), however, simulation results favor NADH as a preferred co-factor for Ld ENR. These results support that the reduction of L. donovani growth in the in vitro and ex vivo drug assays may be due to the interaction of triclosan with Ld ENR, which should be confirmed through enzymatic assays. The results of this study suggest that Ld ENR could be a potential drug target and triclosan as a lead for Leishmaniasis. Communicated by Ramaswamy H. Sarma